2016
DOI: 10.1038/aps.2015.158
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of CDH13 determine the susceptibility to chronic obstructive pulmonary disease in a Chinese population

Abstract: Aim: Adiponectin has been implicated in the development of chronic obstructive pulmonary disease (COPD). The CDH13 gene encodes T-cadherin that is an adiponectin receptor, and genetic variants of CDH13 determine blood adiponectin levels. The aim of this study was to investigate the effects of CDH13 variants on COPD susceptibility in a Chinese population. Methods: Ten single-nucleotide polymorphisms (SNP) in CDH13 were screened using the SNaPshot method in 279 COPD patients and 367 control subjects. Association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 36 publications
(54 reference statements)
1
5
0
Order By: Relevance
“…The SNP rs12922394 is in the first intron of the CDH13 gene and is usually removed during the gene-splicing process. Yuan et al reported that the T allele of rs12922394 was associated with a significantly reduced risk of COPD [44]. In the current study, we found that the T allele of rs12922394 (R = 0.651, 95% CI 0.449-0.942, P < 0.022) was also associated with a reduced risk of COPD, indicating that this variant may protect against COPD development.…”
Section: The Roles Of Rs8192288 Rs20541 and Rs12922394 In Copdsupporting
confidence: 62%
“…The SNP rs12922394 is in the first intron of the CDH13 gene and is usually removed during the gene-splicing process. Yuan et al reported that the T allele of rs12922394 was associated with a significantly reduced risk of COPD [44]. In the current study, we found that the T allele of rs12922394 (R = 0.651, 95% CI 0.449-0.942, P < 0.022) was also associated with a reduced risk of COPD, indicating that this variant may protect against COPD development.…”
Section: The Roles Of Rs8192288 Rs20541 and Rs12922394 In Copdsupporting
confidence: 62%
“…At present, most genetic association studies on COPD risk are focused on determining the individual effects of SNPs and their interaction effects on the disease. Yuan et al found that CDH13 genetic variants determine Chinese individuals’ susceptibility to COPD and could be used as efficient genetic biomarkers for early detection of COPD 18. Xie et al demonstrated that the polymorphisms of WWOX play a role in COPD susceptibility and pulmonary function traits in COPD inheritance.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in allelic and genotypic frequencies of the gene polymorphisms in healthy controls and patients with COPD were compared by χ 2 test, which was also used to evaluate Hardy–Weinberg equilibrium for each individual locus. A multiple logistic regression analysis was performed to correct the significant P -value 18…”
Section: Methodsmentioning
confidence: 99%
“…CCDC67 mRNA, which encodes a 604 amino acid protein containing a coiled-coil domain, was associated with down-regulation in various tumor tissues such as lung, cervix, and gastric cancers [30]. The CDH13 polymorphisms play critical roles in metabolic processes and in the development of metabolic-related diseases and lung diseases such as chronic obstructive pulmonary disease [31, 32]. In most previous PTB GWASs, nongenetic covariates were not considered; however, we could not replicate the associations reported in these studies, even in our unadjusted model.…”
Section: Discussionmentioning
confidence: 99%